Production and use of cassava flour:A new product of future potential in Indonesia - Widowati, Sri; Hartojo, Koes (International Center for Tropical Agriculture, 2001)
Cassava is a perishable commodity. Over-supply occurs every year during the peak harvest season, with varying severity. To overcome the above problem, processing cassava into flour can be an alternative solution. The cassava flour production system in Indonesia is designed as a nucleusplasma model. Cassava flour can substitute for wheat and rice flours as well as cassava starch at varying levels according to the kinds of food products. However, there are still problems in its marketing and distribution. A study on consumer acceptance has been conducted in West Java (115 households) and East Java (100 households and 25 small-scale food industries). Three visits to each respondent were made to collect information on the socio-economic situation, cassava flour utilization, and the level of cassava flour used in the processing of traditional foods, cookies, cakes and crackers. In the various food industries cassava flour was mostly processed into cakes, traditional foods and noodles. Substitution levels ranged from 20 to 100%, depending on the product. The contribution of cassava to the total carbohydrate intake in the diet of urban and rural households was 2.5 and 23%, respectively.